Covalent Organic Frameworks as Electrode Materials for lithium-ion batteries - Zheng, Lijia (Transactions on Environment, Energy and Earth Sciences, 2026)
As renewable energy expands and the electric vehicle market grows, Lithium-ion batteries (LIBs) are playing an increasingly pivotal role in the energy storage sector. Covalent Organic Frameworks (COFs), as an emerging functional material, have widespread applications across various fields. They are viewed as promising electrode candidates for rechargeable batteries because they offer large surface areas, tunable pore structures, high porosity, and facile surface functionalization. This review summarizes recent progress on COFs for lithium‑ion battery electrodes. It examines structural design approaches and functional modifications that enhance electrochemical behavior. It also analyzes the mechanisms by which COFs improve battery performance, for example by facilitating ion transport and by increasing electron conductivity through tailored architectures. The review addresses both cathode and anode uses of COFs, and it highlights recent experimental advances and comparative evaluations across material classes. Finally, it identifies current technical challenges such as synthesis scale-up, intrinsic conductivity limits, pore‑conductivity tradeoffs, and interface stability, and it outlines directions for future work to advance COF-based electrodes toward practical implementations.